2013
DOI: 10.1007/s10811-013-0055-y
|View full text |Cite
|
Sign up to set email alerts
|

Gene cloning and expression profile of a novel carotenoid hydroxylase (CYP97C) from the green alga Haematococcus pluvialis

Abstract: A full-length complementary DNA (cDNA) sequence of ε-ring CHY (designated Haecyp97c) was cloned from the green alga Haematococcus pluvialis by reverse transcription polymerase chain reaction (RT-PCR) and rapid amplification of cDNA ends methods. The Haecyp97c cDNA sequence was 1,995 base pairs (bp) in length, which contained a 1,620-bp open reading frame, a 46-bp 5′-untranslated region (UTR), and a 329-bp 3′-UTR with the characteristic of the poly (A) tail. The deduced protein had a calculated molecular mass o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 58 publications
2
12
0
Order By: Relevance
“…To further study genes encoding CYP97 homologs in green algae, three full-length cDNA sequences of cyp97 homologs, including Haecyp97a , Haecyp97b , and Haecyp97c [84] were isolated from commercial green alga H. pluvialis strain Flotow 1844. Briefly, 1,017- and 984-bp cDNA fragments encoding HaeCYP97A/B were generated by RT-PCR with degenerate primers [see Additional file 5: Table S3].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To further study genes encoding CYP97 homologs in green algae, three full-length cDNA sequences of cyp97 homologs, including Haecyp97a , Haecyp97b , and Haecyp97c [84] were isolated from commercial green alga H. pluvialis strain Flotow 1844. Briefly, 1,017- and 984-bp cDNA fragments encoding HaeCYP97A/B were generated by RT-PCR with degenerate primers [see Additional file 5: Table S3].…”
Section: Resultsmentioning
confidence: 99%
“…A similar, although less pronounced trend was observed under white HL: the highest bch transcriptional level occurred at 54 h of exposure, with 3.3-fold higher compared with the control. Our previous study has demonstrated that zeaxanthin concentrations under blue and white HL treatments were increased markedly and reached their highest levels at 34 h (blue) and 48 h (white) of exposure [84], which is listed in Figure S5 for details [see Additional file 9: Figure S5]. BCH is the mainly enzyme catalyzing the hydroxylation of β -carotene, which produces zeaxanthin associated with the xanthophylls cycle [40,87].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Driven by their nutrition condition, H. pluvialis cells have two different physiological traits: (1) in favorable conditions they are in a green motile stage; (2) under stress conditions (especially nitrogen depletion) the green cells will transform into a reddish non-motile resting stage, coupled with astaxanthin accumulation [19,20,21]. Several key genes related to astaxanthin biosynthesis and stress responding have been cloned and characterized, such as pds [22], CYP97C [23], MnSOD [24], and TR1 [25]. Despite many reports on astaxanthin accumulation of H. pluvialis upon nitrogen depletion [26,27,28], there is no information of its PII protein and associated genetic transcription information on this unicellular microalga.…”
Section: Introductionmentioning
confidence: 99%